Stay with me - Proby, Kristen (Proby, Kristen. With me in Seattle, 2018)
Dominic Salvatore has found a new relationship with his father and the entire Montgomery family. His vineyard, Coppa di Vita, is a success. There's only one thing that eludes him: a certain driven, intelligent, sexy as hell blonde named Alecia, who works tirelessly building her event planning business. Despite the lavish weddings she organizes, Alecia is convinced that the idea of true love is a myth. Welcoming the handsome Italian into her bed, and her life, is a risk, but Dominic isn;t used to taking no for an answer, and it's not long before these two are burning up the sheets and discovering a connection that neither can deny.